Process development for goat milk shrikhand added with kiwi fruit - Pathrikar, A D; Patange, D D; Mote, G V; Udachan, I S; Lokhande, S M (Journal of Postharvest Technology, 2021)
This study was undertaken with the objectives of to develop nutritious goat milk shrikhand added with kiwi fruit pulp. Having the multifarious properties of goat milk and kiwi fruit. Chakka was prepared through goat milk with culture addition. The level of sugar and kiwi fruit pulp in goat milk chakka was optimized through RSM with 13 different samples. The best combination of shrikhand containing 6.85% kiwi fruit pulp and 40% sugar was selected on based on sensory analysis (9 point hedonic)i.e. sensory evaluation score was 8.00, 7.83, 7.91, 7.82, 7.87 for colour, sweetness, taste & flavour, texture & consistency and overall acceptability. The selected concentration was evaluated for sensory, Physico-chemical analysis. Kiwifruit is rich in vitamin C with good source of other nutrients such as folate protein, carbohydrate, potassium, and dietary fibre which is good for health and goat milk contains good amount of fat, protein, lactose and vitamins.